ЭМИГРАНТОЛОГИЯ. НАЦЧНО-ИССЛЕДОВАТЕЛЬСКИЙ ВКЛАД ПОЛЬСКОЙ РУСИСТИКИ - Kowalska-Paszt, Izabela (Przegląd Rusycystyczny, 2016)
EMIGRANTOLOGIA. WKŁAD NAUKOWO-BADAWCZY RUSYCYSTYKI POLSKIEJ Na materiale literacko-kulturowej spuścizny trzech kolejnych fal emigracji rosyjskiej XX stulecia rozpatrzono w artykule dwie funkcje, jakie zdaniem autorki, pełni pojęcie „emigrantologia”, wprowadzony przez Lucjana Suchanka do przestrzeni badawczej wychodźstwa słowiańskiego. Systematyzuje ono obszar intelektualno-naukowej samorefleksji (w tym literaturoznawczej, historiograficznej, filozoficzno-teologicznej, kulturoznawczej), jaka wypracowana została w środowisku emigracji rosyjskiej. Ponadto modeluje potrzebę prowadzenia interdyscyplinarnych, a w nieodległej przyszłości transdyscyplinarnych, studiów nad złożonym fenomenem kulturowym emigracji słowiańskich. W tym kontekście zaprezentowano także ważniejsze kierunki i osiągnięcia badawcze rusycystyki polskiej. EMIGRANTOLOGY. CONTRIBUTION OF RUSSIAN STUDIES IN POLAND TO SCIENCE AND RESEARCH Based on the literary and cultural material, the article discusses two functions played by the term of emigrantology as a legacy of three waves of Russian emigration in the 20th c. The term was introduced by Lucjan Suchanek to the research space of Slavic emigration. It has systematized the area of intellectual and scientific self-reflection (including literary studies, historiography, philosophy and theology, and cultural studies), which developed in the community of Russian emigration. Additionally, the term provides modelling of the need for interdisciplinary and in the nearest future trans-disciplinary studies on the complex cultural phenomenon of Slavic emigrations. In this particular context, the article presents major research directions and achievements of Russian studies in Poland.